Risk factors associated with the outbreak of dengue fever in children in the capital city of Bangladesh - Roy, Kuntal; Halder, Soma; Tajkia, Gule; Roy, Kausik; Chowdhury, Nandita Sur (International Journal of Contemporary Pediatrics, 2025)
Background: Environmental and climatic situations become the risk factors of dengue outbreak. However, the socio–epidemiological and behavioral association with the disease is least explored. The study aims to identify the social and ecological factors as well as public awareness associated with emerging dengue in the capital city of Bangladesh. Methods: This observational study was conducted in the Department of Pediatrics of Anwer Khan Modern Medical College Hospital (AKMMCH), Dhaka, Bangladesh during the period from 4 April, 2019 to 9 September, 2019. Results: In total 105 cases from the groups completed the study. More than half 68.57% found dengue hemorrhagic fever (DHF) fever patients and the least of the 31.43% found dengue shock syndrome (DSS) patients. From the record of personal and hygiene history identified as risk factors of the study, people on the day time mosquito bites found 78.10% positive and 21.90% negative. As well as on using mosquito coils (66.67%) found negative and 33.33% found positive. Use of repellents 88.57% found negative and 11.43% found positive. Remove the stagnant water source 91.43% found negative and 8.57% found positive. Using spray for the insecticide 85.71% had a negative reply and 14.29% had replied positively. On dumping the garbage 88.57% found negative and 11.43% found positive. Again, in home gardening, 84.76% had negative in reply and 15.24% had positive in reply. Conclusions: Personal and hygiene factors play important roles in dengue outbreaks in the capital city of Bangladesh.